Expression of Ca2+‐permeable two‐pore channels rescues NAADP signalling in TPC‐deficient cells. (14th April 2015) - Ruas, Margarida; Davis, Lianne C; Chen, Cheng‐Chang; Morgan, Anthony J; Chuang, Kai‐Ting; Walseth, Timothy F; Grimm, Christian; Garnham, Clive; Powell, Trevor; Platt, Nick; Platt, Frances M; Biel, Martin; et al.
Abstract The second messenger NAADP triggers Ca2+ release from endo‐lysosomes. Although two‐pore channels (TPCs) have been proposed to be regulated by NAADP, recent studies have challenged this. By generating the first mouse line with demonstrable absence of both Tpcn1 and Tpcn2 expression (Tpcn1/2−/−), we show that the loss of endogenous TPCs abolished NAADP‐dependent Ca2+ responses as assessed by single‐cell Ca2+ imaging or patch‐clamp of single endo‐lysosomes. In contrast, currents stimulated by PI(3, 5)P2 were only partially dependent on TPCs. In Tpcn1/2−/− cells, NAADP sensitivity was restored by re‐expressing wild‐type TPCs, but not by mutant versions with impaired Ca2+‐permeability, nor by TRPML1. Another mouse line formerly reported as TPC‐null likely expresses truncated TPCs, but we now show that these truncated proteins still support NAADP‐induced Ca2+ release. High‐affinity [32P]NAADP binding still occurs in Tpcn1/2−/− tissue, suggesting that NAADP regulation is conferred by an accessory protein. Altogether, our data establish TPCs as Ca2+‐permeable channels indispensable for NAADP signalling.